Penerapan Strategi Influencer Marketing melalui Media Sosial - Vania Sekarayodya Raharjo; Iwan Sukoco; Cecep Safa’atul Barkah; Nurillah Jamil Achmawati Novel (Universitas Medan Area, 2023)
The skeptical attitude of consumers has led companies to shift from traditional marketing to influencer marketing. Based on Robert Cialdini's theory of social proof, it is observed that humans tend to make decisions or act based on what others do or think. In the context of influencer marketing, consumer behavior is influenced by the social proof provided by influencers. Dorskin is one of the local skincare brands that has adopted influencer marketing. Therefore, this research aims to explore the influencer marketing strategies applied by Dorskin. The research adopts a descriptive qualitative approach, which uses a case study method. Data collection techniques include interviews as the primary data source and literature studies as the secondary data source. The results show that Dorskin focuses on TikTok and Instagram platforms to market their products, with two main Key Performance Indicators (KPIs) to evaluate the effectiveness of influencer marketing: the number of views and sales. Influencers contribute approximately 70% of Dorskin's total reve-nue.